The Problem of Spontaneous Gestures in the Bible: A Case study of Gestural Poetics - Katsman, Roman (MiKAN, 2008)
The books of the Old Testament are full of descriptions of gestures. In addition to non-verbal elements of behavior such as dress, jewelry, colors and smells, gestures too have quite an important function in the ethics and aesthetics of the "Book of Books". However, biblical gestures have thus far been only inadequately studied (such studies as the work by Uri Ehrlich on gestures in the Jewish rites and the work by Mayer I. Gruber on non-verbal communication in the ancient Middle East made an important though insufficient contribution to the discussion of the issue), this analysis shows that the two manifestations of gesticulation in the Bible, the standard and the spontaneous, are not balanced. The article demonstrates that there is a tendency to de-legitimize and discredit spontaneous gestures. A number of test-cases presented in the paper highlight the varied roles which the poetics of gesture have in the Bible: they establish paradoxical characters and situations, activate the cultural mechanism of making the body disappear, create various narrative levels (by splitting the narrative voice and originating different implied readers), shape the ethical and aesthetic features of saint and sinner, bolster the theological and anthropological positions of monotheism and, ultimately, connect the issue of crime and punishment with an ethical-anthropological conception of the body.